Distributional effects of taxing financial transactions and the low interest rate environment - Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The study aims to assess the distributional effects of taxing financial transactions including a focus on gender. It specifically investigates the impact of the low interest rate environment on tax revenues and distribution. The first part of the study is explorative, aiming to develop a concept for the assessment. This is because the role of low or even negative interest rates is not yet specifically considered in the context of FTT. In the second part, the challenge is to find appropriate data for European countries in order to assess distributional effects. The study also highlights the existing data gaps that prevent a long-term evaluation of FTT with regard to tax revenues, impact, and distributional consequences.
Keywords: G20; H21; H22; H23; 330; risk; European Union; financial transactions; tax burden; social sustainability